Otoczenie nowoczesnych organizacji - Bąkowska-Morawska, Urszula (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Surely we have to deal with the fundamental change of the environment-organization relation. The change is the more visible if we consider functioning of modern organizations for which a customer stays in the center of attention. From the point of view of enterprise the closer environment becomes the interorganizational net of connections in which suitable tradesmen and subcontractors can be found. Openness to relationships with many external subjects permits effectively to gain material and immaterial supplies, and to satisfy more easily changing expectations of customers and different stakeholders. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 29-38